Genetic Pheochromocytoma -a Review - B. Pambinezhuth, F. (Scientific Journal of Medical Science, 2013)
The prevalence of pheochromcytoma in hypertensive patients is less than 1%.Most PHEOs occur sporadically, but a substantial proportionmay be associated with germ line mutations of genes predisposing to thedevelopment of familial syndromes like multiple endocrineneoplasia(MEN),Von-Hippel Lindau(VHL) disease,neurofibromatosis type 1(NF-1),familial paraganglioma/pheochromocytoma (PGL/PHEO) related to geneticmutation encoding the mitochondrial protein succinate dehdrogenase sub units(SDH-BCD) .Screening for genetic mutation is imperative as it may add more onmanagement and surveillance of this patients .This review summarize therelevant data related to this fascinating clinical entity.